Preliminary study on the effect of dry/wet cooling combinations for the sustainable management of water of cooling tower. (27th December 2017) - Lee, Gilbong; Ra, Ho-Sang; Lee, Beomjoon; Lee, Young-Soo; Roh, Chul Woo; Baik, Young-Jin; Cho, Junhyun; Shin, Hyungki
Abstract: Recently, sustainable management of water has received a lot of interest since the shortage of it are one of the major environmental issues. Power plants eject tremendous amount of condensation heat while generating electricity. Water is the most commonly used heat transfer materials. During the heat transfer process, large amount of water is evaporated into the atmosphere. This may cause a severe water management problem. Dry cooling is an alternative cooling method, but it may cause efficiency degrade. In this article, a preliminary strategy for the combination of dry/wet cooling methods was derived.